Pengaruh Kepemimpinan dan Keterampilan Manajerial Kepala Sekolah terhadap Peningkatan Kinerja Guru di SMA Negeri 1 Lubuk Basung - Jontisman, Doni; Sophian, Sophan (Lembaga Yasin AlSys, 2025)
Education plays an important role in forming a generation that is able to answer the challenges of the times, but the quality of teacher performance is still a major problem in many educational units. This study aims to determine the effect of leadership and managerial skills of school principals on improving teacher performance. This study uses a quantitative approach with an associative descriptive research type. The population in this study were all ASN teachers and teachers who had NUPTK in SMA Negeri 1 Lubuk Basung as many as 50 people, with a saturated sample technique. The instrument used is a closed questionnaire containing indicators of each variable, which has been tested for validity and reliability. Data analysis techniques include descriptive analysis, classical assumption tests (normality, multicollinearity, and heteroscedasticity), and multiple linear regression analysis with the help of the SPSS program. The results showed that (1) principals' leadership has a positive and significant effect on teachers' performance, indicated by t-count > t-table and significance <0.05; and (2) principals' managerial skills also have a positive and significant effect on teachers' performance, with similar statistical test results. This study concludes that principals' leadership and managerial skills significantly contribute to improving teacher performance. Therefore, strengthening these two aspects is important in creating a productive and quality school environment.